PENGARUH LAMA PERENDAMAN BENANG TERHADAP KEKUATAN MARLON SEBAGAI MATERIAL PEMBUAT JARING - Elyta Vivi Yanti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Fishing methods increasingly progressing toward more progress with the progress of time. New concepts have been introduced to improve the catch by exploiting fish behavior to aim arrest. Fishing tools exist continuously developed and refined to obtain the maximum catch without forgetting the preservation of aquatic resources are exploited.The purpose and usefulness of the research: to determine the speed of sinking of yarn, absorption is the ability to absorb water during immersion, know the effect of resistance of these materials before and after immersion in water because, to know the elasticity, where elasticity is the ability of a material back to its original length after no change due to tensile force. Usefulness of the research are: to be able to find the resistance of the material marlon as material webs. And can provide information to fishermen about the type of netting material is best. As literature for education and as an to fishing in the future.The method used in this study is completely randomized design (RAL) to calculate the speed of sinking and repeated 12 repetitions, while absorption, elasticity and resilience thread design was completely randomized in a factorial design form.F-test for the sinking speed, absorption, elasticity and resilience yarn ari A factor (number of threads) provides a very real difference. Factor B (soaking time) on the speed and absorption also showed highly significant, while on the elasticity of the factor B (soaking time) was not significantly different, whereas for endurance significantly different. This means that the effect of immersion in the number of different threads marlon provide a very real difference to the strength marlon material in making nets